2010
DOI: 10.1186/1749-799x-5-25
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic extremity arterial injury in children: Epidemiology, diagnostics, treatment and prognostic value of Mangled Extremity Severity Score

Abstract: BackgroundTraumatic paediatric arterial injuries are a great challenge due to low incidence and specific characteristics of paediatric anatomy and physiology. The aim of the present study was to investigate their epidemiology, diagnostic and therapeutic options and complications. Furthermore, the prognostic value of the Mangled Extremity Severity Score (MESS) was evaluated.MethodsIn a retrospective clinical study 44 children aged 9.0 ± 3.2 years treated for traumatic extremity arterial lesions in our Level I t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 29 publications
2
44
1
8
Order By: Relevance
“…This is consistent with literature data where penetrating injuries represent more than 2/3 of injuries in the limbs [1][2][3]. Mommsen et al [6], however, found penetrating wounds in only 31.8% of cases and Jawas et al [7] reported stab lesions in 57% of cases. These findings in our series, although in the line with that of many authors, could be explained by the increase in criminality in our country associated to an increase use of firearms (4 cases) and bladed weapons (8 cases).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This is consistent with literature data where penetrating injuries represent more than 2/3 of injuries in the limbs [1][2][3]. Mommsen et al [6], however, found penetrating wounds in only 31.8% of cases and Jawas et al [7] reported stab lesions in 57% of cases. These findings in our series, although in the line with that of many authors, could be explained by the increase in criminality in our country associated to an increase use of firearms (4 cases) and bladed weapons (8 cases).…”
Section: Discussionsupporting
confidence: 81%
“…Male predominance due to the predominance of trauma in general in men compared to women is the same as in the literature [1][2][3][4][5][6][7][8]. The young age of our patients is also found in several studies.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Зупинка артеріальних кровотеч та реваскуляризації в подальшому ще не гарантують по-вного одужання через стенозування чи оклюзії судин-них анастомозів та дилатацію автовенозних протезів [9,11,18,29,49]. Зауважимо, що загальноприйнятих протоколів лікування травм артерій у дітей на сьогодні немає [1,8,22,27,36,38,46,49].…”
Section: вступunclassified